Lower Incidence of Postdural Puncture Headache With Spinal Catheterization After Accidental Dural Puncture in Obstetric Patients. Issue 3 (September 2015) - Verstraete, S.; Walters, M.A.; Devroe, S.; Roofthooft, E.; Van de Velde, M.
<x xml:space="preserve">Abstract</x> (Acta Anaesthesiol Scand. 2014;58(10):1233–1239)